2010
DOI: 10.2319/062509-354.1
|View full text |Cite
|
Sign up to set email alerts
|

Autotransplantation of Teeth in 215 Patients

Abstract: Objective: To evaluate the success rate of autotransplantation of teeth in consecutive patients and to analyze factors affecting the outcome. Materials and Methods: The subjects consisted of 215 consecutive patients (101 women and 114 men; aged 9.1-56.4 years, median age 15.2 years [P 10 5 11.4, P 90 5 19.7]) who had undergone transplantation of a total of 269 teeth, all by the same surgeon. In patients with multiple transplants, only the first transplant was included, to ensure that all transplanted teeth wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 29 publications
1
117
3
3
Order By: Relevance
“…4 Inflammatory resorption usually commenced from four week after transplantation, while ankylosis between root cementum and the adjacent bone usually occured after 4 months after the procedure. 5 These two types of root resorption were not found in the reported case until 18 months post operatively. This was most probably due to vitality of the pulp tissue and periodontal ligament cells of the transplanted tooth supported by the radiographic evidence of fully formed lamina dura.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…4 Inflammatory resorption usually commenced from four week after transplantation, while ankylosis between root cementum and the adjacent bone usually occured after 4 months after the procedure. 5 These two types of root resorption were not found in the reported case until 18 months post operatively. This was most probably due to vitality of the pulp tissue and periodontal ligament cells of the transplanted tooth supported by the radiographic evidence of fully formed lamina dura.…”
Section: Discussionmentioning
confidence: 57%
“…5 Interestingly, the success rate was reported to increase dramatically in the past two decades. Andreasen et al reported 95% success rate over 13 years of study, Lundberg dan Isaksson achieved 94% in 5 years, Kugelberg et al reported 94% success rate during 4 years of observation, and Cohen showed 98-99% success rate over 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Since the early works of Slagsvold and Bjerke (1, 2) in the 1970s, numerous studies have described techniques, longterm evaluation protocols, indications, contraindications, and success rates better than 90%; however, these results were influenced by certain factors such as the stage of root development, presence or absence of a recipient alveolar socket, age of the patient, type of splint, time left in place, aesthetic and oral health perception, and even subsequent orthodontic treatment (3,5,7,8,(13)(14)(15). Recently, this technique has been described as an alternative treatment in cases of cleft palate and ankylosed upper incisor (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…32 Dikkatli çalışma gerektirmesi, donör dişin periodonsiyumunun zarar görmemesi, alıcı bölgedeki anatomik varyasyonlar, donör dişte meydana gelen kök rezorbsiyonları yöntemin başarısını etkileyen faktörlerdir. 44 Çekim: Ankiloze bir dişin en konvansiyonel tedavisi dişin cerrahi çekimi ve ardından sabit ya da hareketli protezle restore edilmesidir. Çekim kararı, diş restore edilemeyecek kadar harap ise ve infraokluzyon miktarı düzeltilemeyecek kadar şiddetli ise endikedir.…”
Section: Dai̇mi̇ Di̇şlerunclassified